2003
DOI: 10.1038/sj.ijir.3900941
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of antibiotic-soaked, Resist™-coated Bioflex®

Abstract: This study investigates whether a hydrophilic coating (Resistt), designed to inhibit bacterial adherence, applied to inflatable penile prostheses can prolong the effect of intraoperative antibiotics. The activity of antibiotic-soaked Bioflex s (penile prosthetic substrate material) discs with and without Resistt was examined by measuring the zone of inhibition following in vivo exposure in four groups of rabbits: 1, 2, 3 and 5 days' duration of disc implantation. Coated and uncoated discs were soaked in an aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Previous experience using a similar coating on central venous catheters [47•] and hydrocephalic shunts [48] was positive. Hellstrom et al [49] investigated whether this hydrophilic coating (resist) applied to inflatable penile prostheses can prolong the effect of intraoperative antibiotics. The activity of the antibiotic-soaked Bioflex (penile prosthesis substrate material) discs with and without resist was examined by measuring the zone of inhibition following in vivo exposure in rabbits.…”
Section: Antibiotic-coated Inflatable Penile Prosthesesmentioning
confidence: 99%
“…Previous experience using a similar coating on central venous catheters [47•] and hydrocephalic shunts [48] was positive. Hellstrom et al [49] investigated whether this hydrophilic coating (resist) applied to inflatable penile prostheses can prolong the effect of intraoperative antibiotics. The activity of the antibiotic-soaked Bioflex (penile prosthesis substrate material) discs with and without resist was examined by measuring the zone of inhibition following in vivo exposure in rabbits.…”
Section: Antibiotic-coated Inflatable Penile Prosthesesmentioning
confidence: 99%
“…Unlike the antibiotic coating, the hydrophilic gel is permanently bound to the prosthesis, and should not elute after a short time, perhaps enabling the prosthesis to be periodically recharged with antibiotics given by an oral or intravenous route. In vivo experiments have shown that the Resist coating prolongs antibiotic efficacy [75], but data on its bacterial antiadherence properties and clinical data are not yet available.…”
Section: Penile Prosthetic Devicesmentioning
confidence: 99%
“…This coating absorbs surgeon chosen intraoperative antibiotics that can elute into surrounding tissues over 24-72 h to further decrease infection (Hellstrom et al, 2003). Mansouri and colleagues compared the spectrum and durability, both in vitro and in vivo of the hydrophilic coated prosthesis dipped in vancomycin and the InhibiZone implants, and found that the antibiotic pre-impregnated prosthesis had a broader spectrum in vitro and a more durable antimicrobial activity in vitro and in an animal model than implants dipped in vancomycin (Mansouri et al 2009).…”
Section: Hydrophilic Coatingmentioning
confidence: 99%